Pseudogracilibacillus auburnensis gen. nov., sp. nov., isolated from the rhizosphere of Zea mays - Glaeser, Stefanie P.; McInroy, John A.; Busse, Hans-Jürgen; Kämpfer, Peter (International Journal of Systematic and Evolutionary Microbiology, 2014)
A Gram-positive-staining, aerobic, endospore-forming bacterium, strain P-207T, was isolated from a rhizosphere soil sample in Auburn, AL, USA. On the basis of 16S rRNA gene sequence comparisons, strain P-207T was grouped in the vicinity of representatives of the genera Virgibacillus , Ornithinibacillus , Cerasibacillus , Lentibacillus and Oceanobacillus , but could not be assigned clearly to any of these genera. The highest similarity was found to the sequence of Virgibacillus carmonensis LMG 20964T (94.4 %); however, the 16S rRNA gene sequence similarity to the type strain of the type species of Virgibacillus , Virgibacillus pantothenticus , was only 92.9 %. The quinone system of strain P-207T consisted predominantly of menaquinone MK-7. The polar lipid profile exhibited the major lipids diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine and moderate to minor amounts of several unidentified phospholipids, glycolipids and phosphoglycolipids, an aminophospholipid and an aminolipid. The diagnostic diamino acid of the peptidoglycan was meso-diaminopimelic acid and the polyamine pattern contained predominantly spermidine and spermine. The major fatty acids were anteiso-C15 : 0, anteiso-C17 : 0, iso-C16 : 0 and iso-C15 : 0. The G+C content of the genomic DNA was 34 mol%. Because of the low sequence similarity of strain P-207T to all representatives of Virgibacillus , Ornithinibacillus , Cerasibacillus , Lentibacillus and Oceanobacillus , which was always <95 %, and its unique lipid pattern, we propose that strain P-207T represents a novel species in a new genus, for which the name Pseudogracilibacillus auburnensis gen. nov., sp. nov. is proposed. The type strain of Pseudogracilibacillus auburnensis is P-207T ( = CCM 8509T = LMG 28212T = CIP 110797T).